PENGEMBANGAN MEDIA DIGITAL STORYTELLING PADA PEMBELAJARAN BAHASA INDONESIA SDN 158 PALEMBANG - Muhammad Sirajuddin; Liza Murniviyanty; David Budi Irawan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Learning media is an important factor in the learning process. One of the problems of education in Indonesia is the limited use of learning media in the learning process. The purpose of this study was to determine the validity, practicality, and effectiveness of digital storytelling media in Indonesian language learning at SDN 158 Palembang. The research method used was the R&D (Research and Development) method with the ADDIE development model. The results of the study showed that the validity aspect obtained from the validator or experts obtained an average percentage of expert validation results of 92% so that it falls into the